Project-Based Assessment Models for Senior High School Grade XI - Vivi Muryanti (Indonesian Journal of English Language Studies (IJELS), 2015)
Project-Based Learning is one of the approaches of teaching English which supports the scientific approach of Curriculum 2013. This approach can bring some benefits to the students namely promoting the comprehensible input and output and gaining successful experiences with the real world, and also supporting learner centeredness during the learning process. However, the implementation of this approach still has some problems particularly in terms of appropriate kinds of project and the way to assess the students‟ progress and achievement. Therefore, this article proposes the projects and the assessment models for Senior High School Grade XI as an alternative to overcome the problems of the implementation of Project-Based Learning in Curriculum 2013.